2014
DOI: 10.3892/ijmm.2014.1766
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of muscone on cardiac remodeling in a mouse model of myocardial infarction

Abstract: Musk has been traditionally used in East Asia to alleviate the symptoms of angina pectoris. However, it remains unclear as to whether muscone, the main active ingredient of musk, has any beneficial effects on persistent myocardial ischemia in vivo. The aim of the present study was to investigate whether muscone can improve cardiac function and attenuate myocardial remodeling following myocardial infarction (MI) in mice. Mice were subjected to permanent ligation of the left anterior descending coronary artery t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 40 publications
(36 reference statements)
3
30
0
Order By: Relevance
“…The occurrence of autophagy and apoptosis is accompanied by the inhibition of AKT/mTOR signalling pathway . Moreover, studies have shown that muscone can induce phosphorylation of AKT during myocardial infarction in mice . Consistent with this phenomenon, our study discovered that the expression of phosphorylated AKT and mTOR was inhibited in RSC 96 cells treated with HG, while the expression trend of phosphorylated AKT and mTOR was reversed after treated with muscone.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The occurrence of autophagy and apoptosis is accompanied by the inhibition of AKT/mTOR signalling pathway . Moreover, studies have shown that muscone can induce phosphorylation of AKT during myocardial infarction in mice . Consistent with this phenomenon, our study discovered that the expression of phosphorylated AKT and mTOR was inhibited in RSC 96 cells treated with HG, while the expression trend of phosphorylated AKT and mTOR was reversed after treated with muscone.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have demonstrated that muscone has anti‐apoptotic effect on myocardial remodelling in myocardial infarction mice . It has been reported that apoptosis of SCs is one of the characteristics of DPN .…”
Section: Discussionmentioning
confidence: 98%
“…Muscone is a compound found in traditional herbs that is used in China for preventing several diseases and for decreasing the onset of symptoms occurring in patients [4,5,6,7,8,9]. In this study, a preliminary toxicity profile of muscone is presented with extensions to the inductive propensities of the latter compound on CYP1A2 and CYP3A4 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although musk was initially obtained from natural sources, its extensive use has led to chemical synthesis that resulted in the emergence of 3 major classes of musk compounds, notably aromatic nitro compounds, polycyclic musk compounds, and macrocyclic musk compounds [4]. Muscone is one of the macrocyclic musk compounds that is well known for the characteristic odor of musk and has been extensively studied as a natural preventive medicine for a variety of disorders [4,7,8,9]. In the 2012 version of the national pharmacopoeia, approximately 10% of Chinese medicines, such as Angongniuhuang and Suhexiang pills, contained musk.…”
Section: Introductionmentioning
confidence: 99%
“…Muscone (MUS), 3-methylcyclopentadecanone, is the main ingredient of musk ( Figure 1A). It is used to treat myocardial infarction (Wang et al, 2014;Du et al, 2018), relieve pain, and promote fractures . Furthermore, it has been proved to have anti-inflammatory effects on multiple systems (Wang et al, 2014;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%